Cover Image, Volume 38, Issue 3. Issue 3 (16th April 2018) - Chen, Changmai; Yang, Zhenjun; Tang, Xinjing
Abstract : On the cover : The cover image, by Changmai Chen et al., is based on the Review Article Chemical modifications of nucleic acid drugs and their delivery systems for gene‐based therapy, https://doi.org/10.1002/med.21479 .